Quality of care in long-term care departments in mental health facilities across the Czech Republic. (6th August 2018) - Kalisova, Lucie; Pav, Marek; Winkler, Petr; Michalec, Jiri; Killaspy, Helen
Abstract: Background: In the region of Central and Eastern Europe, long-term departments at psychiatric hospitals provide a large proportion of the care for people with complex mental health needs. The System of United Psychiatric Rehabilitation (S.U.P.R.) project focussed on the implementation of a complex set of interventions of psychosocial rehabilitation to increase the quality of care. The aim of this study was to assess the effect of the S.U.P.R. psychosocial rehabilitation programme on the quality of care at the longer-term inpatient psychiatric departments. Methods: All 12 psychiatric hospitals in the Czech Republic were asked to participate in the study. A 'before and after' design was adopted to evaluate the impact of the S.U.P.R. programme. Quality of care was assessed using the internationally validated, web-based tool, QuIRC (Quality Indicator for Rehabilitative Care), which provides percentage scores (0–100%) on seven domains of care and an overall mean quality score. Results: Fourteen long-term wards of 12 psychiatric hospitals for adults in the Czech Republic participated in the S.U.P.R. project. The mean total QuIRC scores were relatively low at the start of the project (range 33% to 53%) but all domain scores increased two years after the S.U.P.R. programme was implemented (range 44% to 62%). Staff feedback was generally positive about the programme, but inadequate staffing was an impediment to its success. Conclusion: Implementing a modern concept for psychosocial rehabilitation aimed at progressing the recovery of people with complex mental health problems can improve the quality of care in longer term inpatient settings.